Social security administration: towards one of the reserves of sustainability - Grishchenko, Natalia (Lodz University of Technology Press, 2021)
In this paper, we consider approaches, trends and expenditures in social security administration (SSA), mainly using the countries of the European Union. The potential of SSA in the current context are largely underestimated. We focus on the institutions and approaches in SSA, the comparative evaluation of expenditures and administrative costs of SSA in the EU countries, and related issues and challenges of SSA based on the comparison of different approaches. Drawing on this context, we define research questions as: What are the leading institutions and approaches in SSA? Whether and in what a reserve of SSA is present for social security sustainability? We use an analytic approach, data and assumptions about how SSA potential is influencing social security sustainability.
Keywords: social security administration (SSA); SSA in the EU countries; social security expenditures; social insurance; social security institutions